ON THE BEGINNINGS AND PARTICULARITIES OF THE LITHUANIZATION OF CITIES - Safronovas, Vasilijus (Sociologija. Mintis ir veiksmas, 2016)
In the long nineteenth century, the process of the nationalization of cities, perceived as the efforts of people identified themselves with particular national community to get established in the cities in a variety of ways, manifested itself throughout a large part of the East Central Europe. In almost all cases such nationalization meant the transformation of a pluricultural city into “one’s own”, allegedly belonging to one nation. In European historiography, research of this process is far from being innovative. Still, investigation of the Lithuanians’ efforts to get established in the cities are gaining momentum only now, while a number of questions, particularly those concerned the initial stages of the process, remain unanswered so far. On the basis of researches into this process in their contemporary stage of development, the article examines, whether the efforts of Lithuanians to get established in the urban areas can be summarized and contextualised according to some general European example. The author aims to answer the question of whether the Lithuanization of cities was somehow exceptional in the regional context. He also examines the factors that led to the specifics of that Lithuanization.
Keywords: urbanization; nationalization of cities; Lithuanization of cities; ideology